The effect of COVID-19 and the wage compensation measure on income-related gender disparities. Issue 2 (3rd July 2022) - Laurimäe, Merilen; Paas, Tiiu; Paulus, Alari
ABSTRACT: Many countries implemented wage compensation measures during the COVID-19 crisis to alleviate income losses and avoid employment reductions. We focus on the gender dimension of incomes in Estonia, which has been grappling with the highest gender wage gap in Europe, and investigate whether the crisis and related wage compensation may have worsened existing gender imbalances. Using detailed administrative datasets and EUROMOD microsimulation model, we show that the COVID-19 crisis had a significant negative effect on employment income for both men and women, but the wage compensation implemented in 2020 appeared to cushion these effects. Income losses were slightly higher for men, but the cushioning effect of the compensation was higher for women. Overall, income-related gender disparities did not change significantly during the crisis. Still, the wage compensation measure has contributed to preventing income-related gender disparities increasing further, particularly in the hotels and restaurants sector and wholesale and retail trade sector.